Numerical study on the hemodynamics of patient‐specific carotid bifurcation using a new mesh approach. (30th March 2018) - Pinto, S.I.S.; Campos, J.B.L.M.; Azevedo, E.; Castro, C.F.; Sousa, L.C.
Abstract: The definition of a suitable mesh to simulate blood flow in the human carotid bifurcation has been investigated. In this research, a novel mesh generation method is proposed: hexahedral cells at the center of the vessel and a fine grid of tetrahedral cells near the artery wall, in order to correctly simulate the large blood velocity gradients associated with specific locations. The selected numerical examples to show the pertinence of the novel generation method are supported by carotid ultrasound image data of a patient‐specific case. Doppler systolic blood velocities measured during ultrasound examination are compared with simulated velocities using 4 different combinations of hexahedral and tetrahedral meshes and different fluid dynamic simulators. The Lin's test was applied to show the concordance of the results. Wall shear stress–based descriptors and localized normalized helicity descriptor emphasize the performance of the new method. Another feature is the reduced computation time required by the developed methodology. With the accurate combined mesh, different flow rate partitions, between the internal carotid artery and external carotid artery, were studied. The overall effect of the partitions is mainly in the blood flow patterns and in the hot‐spot modulation of atherosclerosis‐susceptible regions, rather than in their distribution along the bifurcation. Abstract : A suitable mesh to simulate carotid blood flow in humans has been investigated. A novel mesh generation, hexahedral cells in the center and tetrahedral in the artery wall coupled with ANSYS software, is proposed to solve the relevant flow features and reduces computation time. Lin's test shows the suitability of the method, comparing measured blood velocities with simulated using the new approach and 3 recurrent methods. The wall shear and helicity descriptors, emphasizing atherosusceptible zones, highlight the methodology performance.